Effect of Donor Variables on Platelet Yield Among Donor Undergoing Plateletpheresis at Transfusion Medicine Department, Dhaka Medical College Hospital (Experience of 350 Procedures) - Karim, Shanaz; Hoque, Md Mazharul; Hoque, Ehteshamul; Islam, Kashfia; Mamun, ABM Al (Journal of Dhaka Medical College, 2021)
Background: The platelet transfusions help in prevention of bleeding related complications and thus prevents morbidity and mortality in thrombocytopenic patients. Platelet transfusion plays an important role in the treatment of haematological, oncological, surgical, and transplant patients. Platelets are transfused by two methods i) by fractionation of whole blood and ii) by platelet apheresis. Over the last decade there has been a trend towards the use of SDPs rather than pooled random donor platelets in thrombocytopenic patients. Optimization of platelet yield is an emerging issue to identify factors which may help in selecting donors to obtain higher platelet yields in shorter time and consequently better clinical outcome. Objective: The quality of single donor platelets (SDP) in terms of yield influences the platelet recovery in the recipient. The aim was to identify the SDP donor factors that influence platelet yield. Methods: The study was undertaken at transfusion medicine department, DMCH from 1st January 2017 to 31st December 2017. The study included 350 plateletpheresis procedures. All procedures were performed according to manufacturer’s manual and standard operating procedure. Results: During the period of study, 350 platelet pheresis donors were studied. All of the donors were male. Platelet yield showed high statistical significance with pre donation platelet count and its indices. (p=0.000). Statistical significant negative correlation was seen between pre donation Hb concentration and the platelet yield. (p =0.005). No statistical significance was seen height (p=0.933), weight (p=0.760) of donor on platelet yield. Conclusion: Platelet recovery in the patient is influenced by the transfused dose of platelets, which in turn is dependent on the quality of the platelet product in terms of yield. Various donor factors such as pre donation platelet count and haemoglobin concentration may affect platelet yield. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 179-183